Neural Evidence of Superior Memory: How to Capture Brain Activities of Encoding Processes Underlying Superior Memory - Yoon, Jong-Sung; Harper, Jeremy; Boot, Walter R.; Gong, Yanfei; Bernat, Edward M. (Frontiers in Human Neuroscience, 2019)
Relatively little attention has been paid to the neural basis of superior memory despite its potential in providing important insight into efforts to improve memory in the general population or to offset age-related cognitive decline. The current study reports a rare opportunity to reproduce and isolate specific neural activities directly associated with exceptional memory. To capture the brain processes responsible for superior memory, we returned to a laboratory task and analytic approach used to explore the nature of exceptional memory, namely, digit-span task combined with verbal protocol analysis. One participant with average memory received approximately 50 hours of digit-span training and the participant’s digit-span increased from normative (8 digits) to exceptional (30 digits). Event-related potentials were recorded while the participant’s digit span increased from 19 to 30 digits. Protocol analysis allowed us to identify direct behavioral indices of idiosyncratic encoding processes underlying the superior memory performance. EEG indices directly corresponding to the behavioral indices of encoding processes were identified. The results suggest that the early attention-related encoding processes were reflected in theta and delta whereas the later attention-independent encoding processes were reflected in time-domain slow-wave. This fine-grained approach offers new insights into studying neural mechanism mediating superior memory and the cognitive effort necessary to develop it.